On chip purification of hiPSC-derived cardiomyocytes using a fishnet-like microstructure. (7th September 2016) - Li, Xin; Yu, Leqian; Li, Junjun; Minami, Itsunari; Nakajima, Minako; Noda, Yuichiro; Kotera, Hidetoshi; Liu, Li; Chen, Yong
Abstract: Human induced pluripotent stem cells (hiPSCs) can be differentiated at high efficiency into cells of a targeting type but the resulting cell population has to be of high purity for clinical therapies to avoid teratomas. Herein, we report a microfluidic device with integrated and surface functionalised fishnet-like structures for specific cell capture. With the help of a flow derivation surface pattern, cells in solution are forced to cross the fishnet-like structure, resulting in high efficiency and selective retention of a chosen cell population. A suspension of hiPSCs and hiPSC-derived cardiomyocytes were used for device function validation. We found that a hiPSC capture rate over 80% can be achieved along with a remarkable increase in the CM population rate in the recovered suspension without affecting cell viability.